Palladium‐Nanoparticles‐Catalyzed Oxidative Annulation of Benzamides with Alkynes for the Synthesis of Isoquinolones. Issue 11 (29th March 2017) - Sharma, Nidhi; Saha, Rajib; Parveen, Naziya; Sekar, Govindasamy
Abstract: A novel method to synthesize isoquinolones via oxidative annulation of N ‐alkoxy benzamides and alkynes using binaphthyl‐stabilized palladium nanoparticles (Pd‐BNP) as catalyst has been developed. This methodology affords various isoquinolone derivatives in good to excellent yields with high regioselectivities in the presence of air as oxidant. N ‐Methoxybenzothioamide was also found to undergo oxidative annulation with alkyne successfully and provided a sulfur analogue of isoquinolones in moderate yields. The Pd‐BNP catalyst was easily recovered and reused up to four times without any apparent agglomeration. Abstract :